Penerapan Metode Analitical Hierarchy Process Dalam Sistem Pendukung Keputusan Untuk Penilaian Siswa Berbasis Kompetensi - Wahyu Azhar Ritonga; Sudi Suryadi; M. Fauzi Romadhon Marpaung; Raden Sri Ayu Ramadhana; Shabrina Rasyid Munthe (LPPM Universitas Al Washliyah Labuhanbatu, 2022)
To develop the potential of students, in every curriculum, evaluation is very important to pay attention to, considering evaluation as a tool to assess and measure the level of students' abilities in addition to understanding the changes that occur in students' daily lives. The 2013 curriculum involves several criteria that must be taken because there are three domains of competence to be assessed, namely attitude competence, knowledge competence, and skills competence. Meanwhile, inclusion of students with achievements in the report card supplement sheet or Study Results Card (KHS) is very important as a benchmark for students in improving their achievements, as well as as a reference for entering high school as usual and screening for scholarships. Therefore, it is necessary to find a method that usually chooses weighted criteria so that it can be used as a reference in determining outstanding students.